Manual aspiration in the biopsy-side down position to deal with delayed pneumothorax after lung biopsy - Zeng, Li-Chuan; Yang, Han-Feng; Xu, Xiao-Xue; Xie, Ming-Guo; Liao, Hua-Qiang; Zhang, Yu-Dong; Wang, Qu; Du, Yong (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Background: To assess the effect of aspiration in the biopsy-side down position to deal with delayed pneumothorax after computed tomography (CT)-guided lung biopsy. Methods: A retrospective review was performed of the 236 delayed pneumothorax patients who underwent CT-guided transthoracic needle biopsies (TTNBs). Asymptomatic minimal pneumothorax patients were managed conservatively. Manual aspirations were applied for symptomatic cases with minimal pneumothorax and all cases with moderate to large pneumothorax. Patients were included into two groups: in group A (35 patients), aspiration was performed in the same position as the biopsy, while in group B (54 patients), patients were turned to the biopsy-side down position (from supine to prone or vice versa), and aspiration was conducted. The ef cacy of two approaches was evaluated. Results: One hundred forty-seven (62.3%) asymptomatic cases resolved without treatment. Distance between parietal and visceral pleura before and after aspiration were 4.24±1.87 and 1.93±2.33 cm for group A, 3.92±1.31 and 0.98±1.50 cm for group B, respectively. Volume of aspirated air in group A and group B were 735.4±231.8 and 434.8±320.3 mL, respectively. Complete lung expansion was detected in 28.6% (10/35) and 38.9% (21/54) for group A and group B, respectively. The overall effective rate and failure rate were 74.3% (26/35) and 25.7%(9/35) for group A, 92.6% (50/54) and 7.4% (4/54) for group B, respectively, which have signi cant statistic difference (P